Penguatan Budaya Kerja Dan Kepemimpinan Dalam Mengelola Keberagaman Sumber Daya Manusia Di BMR Sign - Sayyidatina Fatimah; Velly Oktaviani; Naslizah; Zahra Tsaniyah Putri Melani; Fauzul Majid (Shofanah Media Berkah, 2025)
This study aims to explain how work culture and leadership style play a role in managing human resource diversity at BMR Sign, a digital printing company that employs employees with diverse educational backgrounds and experiences. The issues raised relate to how business owners build a conducive work culture and maintain effective communication in a diverse work environment. The study used a qualitative descriptive method through in-depth interviews with the BMR owner as the key informant. Data analysis was conducted thematically to identify leadership patterns, organizational dynamics, and cross-cultural negotiation strategies. The results show that leadership based on religious values, kinship, and discipline can foster a harmonious and productive work culture. Employee diversity can be managed through open communication, regular briefings, periodic evaluations, and interpersonal approaches. Furthermore, a friendly, professional, and adaptive communication strategy helps BMR build trust with customers from various cultural backgrounds. These findings confirm that a religious-humanistic work culture and participatory leadership contribute to strengthening organizational performance and business sustainability.